Community transition at younger ages contributes to good cognitive function outcomes in long‐term hospitalized patients with schizophrenia spectrum disorder: A 15‐year follow‐up study with group‐based trajectory modeling. Issue 2 (4th November 2019) - Kida, Hisashi; Niimura, Hidehito; Nemoto, Takahiro; Ryu, Yonosuke; Sakuma, Kei; Mimura, Masaru; Mizuno, Masafumi
Abstract : Aim: Cognitive dysfunction is a core symptom of schizophrenia spectrum disorder, but the reported long‐term cognitive outcomes are heterogeneous. This study aimed to elucidate the long‐term trajectories of patients with schizophrenia spectrum disorder who transitioned to community dwelling with integrated care, and to identify predictors of successful community reintegration. Methods: After the closure of a psychiatric hospital, 78 patients with schizophrenia spectrum disorder (mean age: 54.6 years) were transferred to the community. We assessed patients' cognitive function over 15 years with the Mini‐Mental State Examination (MMSE) and analyzed the scores every 3 years. Forty‐four patients completed all assessments. Results: The mean MMSE score at discharge was 25.8, which changed to 26.8 after 3 years and 25.3 after 6 years. After 12 and 15 years, it had decreased significantly to 23.3 and 23.0, respectively. Group‐based trajectory modeling identified two groups of patients: a 'poor‐outcome' group (63.4%), showing a decline in scores after maintaining post‐discharge levels for several years, and a 'good‐outcome' group (36.6%), maintaining post‐discharge scores after showing improved scores. Conclusion: Considering the significant difference in age between the aforementioned groups ( P = 0.040), we suggest that community transitions at younger ages contribute to better cognitive function and adaptation to community life. Even middle‐aged and elderly patients with chronic schizophrenia spectrum disorder showed improved or maintained cognitive function at least 3 years after discharge, and the good‐outcome group maintained cognitive function over 15 years. Improvements were dominated primarily by age at discharge, with cognitive function being maintained longer in patients in the good‐outcome group.